2022
DOI: 10.1038/s41598-021-03867-8
|View full text |Cite
|
Sign up to set email alerts
|

Predicting students’ performance in e-learning using learning process and behaviour data

Abstract: E-learning is achieved by the deep integration of modern education and information technology, and plays an important role in promoting educational equity. With the continuous expansion of user groups and application areas, it has become increasingly important to effectively ensure the quality of e-learning. Currently, one of the methods to ensure the quality of e-learning is to use mutually independent e-learning behaviour data to build a learning performance predictor to achieve real-time supervision and fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 47 publications
(33 reference statements)
1
18
0
1
Order By: Relevance
“…Os estudos A9 e A12 trabalham com o ensino online, apresentando a viabilidade de ensino sistematizado e em módulos de aprendizagem sobre a violência contra a pessoa idosa. Os treinamentos on-line ou e-learning são realizados pela integração dos conhecimentos de educação e tecnologia da informação, e a sua utilização vem proporcionando maior equidade educacional (Qiu et al, 2022).…”
Section: Discussionunclassified
“…Os estudos A9 e A12 trabalham com o ensino online, apresentando a viabilidade de ensino sistematizado e em módulos de aprendizagem sobre a violência contra a pessoa idosa. Os treinamentos on-line ou e-learning são realizados pela integração dos conhecimentos de educação e tecnologia da informação, e a sua utilização vem proporcionando maior equidade educacional (Qiu et al, 2022).…”
Section: Discussionunclassified
“…Sustainable personalized learning can be accomplished through continuous analysis of data relating to assessments, user interaction, and learning behavior. Certain characteristics, such as learning style [122] [123] [124], knowledge level [125] [126], performance/score [127], learning goal [128], and learner profile [34], can provide insightful feedback for the learner's journey that derives the individualized learning paths [129] . Meta cognitive evaluation of an individual's learning can greatly encourage learner to further progress in any learning environment.…”
Section: Assessments and User Behaviourmentioning
confidence: 99%
“…The results showed that the subjects of the 1st and 3rd semesters had strong relationship with final CGPA. Based on existing e-learning methods, behavior classification based E-learning Performance (BCEP) model and process behaviour classification (PBC) model were proposed by 23 . The experiments were conducted on Open University Learning Analytics Dataset (OULAD) to predict e-learning performance and the results showed that the proposed models were performed better than the traditional methods.…”
Section: Literature Reviewmentioning
confidence: 99%